2019
DOI: 10.5371/hp.2019.31.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Functional Recovery and Stem Stability after Hip Arthroplasty with a Short Metaphyseal Stem in Elderly Patients with Osteoporotic Femoral Neck Fractures

Abstract: PurposeShort stems have recently become widely used; however, concerns about the initial secure fixation of a short stem in osteoporotic bone remain. The aim of this study was to evaluate the short-term clinical and radiological results of using a short cementless metaphyseal stabilizing tapered stem for senile osteoporotic femoral neck fractures.Materials and MethodsThirty-eight arthroplasties (31 bipolar hemiarthroplasties and 7 total hip arthroplasties) were performed for osteoporotic femoral neck fractures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…In this study, we observed radiolucent lines in 55.8% of all hips 1 year after surgery, half of which (50%) occurred in zone 1. A previous study using the Tri-Lock BPS noted the occurrence of radiolucent lines in zone 1 in 42.1% of the operated hips at 2.9 years after surgery, 25 which is similar to our results. We also found a marked decrease in the frequency of radiolucent lines in 9.5% of patients, 5 years postoperatively.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we observed radiolucent lines in 55.8% of all hips 1 year after surgery, half of which (50%) occurred in zone 1. A previous study using the Tri-Lock BPS noted the occurrence of radiolucent lines in zone 1 in 42.1% of the operated hips at 2.9 years after surgery, 25 which is similar to our results. We also found a marked decrease in the frequency of radiolucent lines in 9.5% of patients, 5 years postoperatively.…”
Section: Discussionsupporting
confidence: 92%
“…Among arthroplasties for the treatment of intracapsular femoral neck fractures also the usage of short stem prothesis showed good results [ 24 ]. Even in patients with osteoporotic fractures sufficient results with stable bony integration was found [ 25 ]. Among the osteosynthesis the dynamic compression screw was mostly used, but number of procures decreases with increasing patient age.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis of the results of patients under 70 years and older than 70 years has not shown significant differences (p > 0.05) and it is shown that there is no contraindication in the use of short stems only due to age. 2527…”
Section: Discussionmentioning
confidence: 99%